Variation in Luminescence Characteristics and Paramagnetic Defect Centres in Fine-Grained Quartz From a Loess-Palaeosol Sequence in Tajikistan: Implications for Provenance Studies in Aeolian Environments - Dave, Aditi K.; Timar-Gabor, Alida; Scardia, Giancarlo; Safaraliev, Nosir; Fitzsimmons, Kathryn E. (Frontiers in Earth Science, 2022)
Trapped charge characteristics in quartz are of increasing interest for their utility as indicators of sediment provenance. These include sensitivity of optically stimulated luminescence (OSL) and thermoluminescence (TL) signal and paramagnetic E1’ defect centre in quartz. Up until now, these methods have largely been used independently in provenance investigations, especially in aeolian systems. Variations in quartz OSL and TL signal sensitivity in loess-palaeosol sequences has been linked to shifts in sediment source corresponding to climatic fluctuations. However, the processes responsible for observed variation in OSL and TL sensitivity in quartz, including its link to the original rock source and/or its sedimentary history, remains a topic of contention. On the other hand, the intensity of E1’ defect centre in quartz is known to reflect the provenance of quartz, and is also routinely utilised as a provenance indicator in aeolian studies. In this study we aim to understand the variations in E1’ intensity and OSL (and TL) sensitivity by direct comparison of these characteristics in fine-grained quartz from a c. 60 m-thick loess-palaeosol sequence in Tajikistan. In doing so, we investigate the natural processes that may have led to variability in trapped-charge characteristics over the c. 500 ky timespan covered by the sequence. Our results suggest that apart from the inherent link to its provenance signature, the observed luminescence sensitivity of quartz especially in loess-palaeosol sequences are largely influenced by depositional and post-depositional processes during soil formation.